Production performance and milk fatty acid profile as affected by cold-pressed oilseed cakes and sainfoin in Latxa dairy ewes - Pascual A.; Garcia-Rodriguez I.; Goiri I.; Pineda-Quiroga C.; Atxaerandio R.; Ruiz R. (Innovation for sustainability in sheep and goats, 2019)
A lactation study utilizing 72 dairy ewes was performed to determine effects of cold-pressed oilseed cakes (CPOC), including cold-pressed sunflower cake and cold-pressed rapeseed cake, and their interaction with tanniferous sainfoin hay, on production performance and milk fatty acid profile. A 2 x 3 factorial arrangement involving two forages (fescue and sainfoin hay) and 3 experimental concentrates was used. Concentrates were formulated to contain cold-pressed rapeseed cake (RPS), cold-preseed sunflower cake (SUN) or palm (CTR) as fat sources and to provide equal amounts of crude protein fat and energy. SUN reduced milk total saturated fatty acids (SFA) compared to CTR with both non-tanniferous (FES) and tanniferous (SAIN) forages, while RPS only reduced SFA with SAIN. Polyunsaturated fatty acids were increased with SUN and RPS and SAIN. SUN increased n6:n3 ratio compared to CTR (+54%) and RPS (+62%) and SAIN reduced this ratio compared to FES (-27%). Concentrate did not affect milk production. In conclusion, healthier milk can be obtained with CPOCs. Nevertheless the forage used in the ration seems to be of great importance.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)